An exploratory study of the perception and attitudes of social work students towards mental health in Malawi - Mkandawire, Thandiwe (Department of Social Development, 2017)
This phenomenological study seeks to understand the perceptions and attitudes of Social Work students towards mental health at the Catholic University in Malawi. This study explores perceptions and attitudes towards persons with mental health problems; effective intervention strategies for mental health problems and help seeking behavior. These objectives are supported by two theoretical frameworks: Recovery Theory in relation to mental health and the Attitudes Theory. The research method is an exploratory qualitative design with multiple participants. Seventeen Social Work students were the unit of study, selected according to a purposive and discriminant sampling design. Data was collected using a semi-structured interview schedule, and recorded during an in-depth interview. This study brought to the fore the perceptions and attitudes of Social Work students of mental health. Participants indicated that they perceive mental health problems as a real illness citing genetics and biological factors; drug and alcohol abuse; and witchcraft/spirit possessions as the causes of mental health problems, with the commonality of mental health problems consolidating them as a real disease. Participants cited cognitive abilities and normality as indicators of mental health problems. Participants felt that recovery; interpersonal relationships and inclusion are significant aspects of mental health problems. Participants felt that effective treatment was dependent on the severity of the mental health problem, citing link to services and counseling as the roles of Social Workers in providing effective intervention. Participants indicated that they would seek professional help as well as encouraging their clients to seek professional help. Participants indicated that discrimination and segregation presents as a barrier for disclosure of mental health problems as well as treatment. Participants also indicated aggression and awareness as aspects of mental health problems. Participants stated that they can easily recognize psychosis.